Unsettled territory - Parr, Tara L., author; Wassell, Harold, advisor; Runyan, William E., committee member; Lundberg, Thomas R., committee member; Berland, John C., committee member (Colorado State University. Libraries, 1986)
In a surreal manner, my work tests the burgeoning notion of art as life and life as art. Artistic effort to be more real than reality has a long tradition, but it is beginning with Marcel Duchamp that the particular turn of mind which fascinates me becomes evident in art. The overwhelming doubt in regard to the finality of a proposition is the motivation for my representation of experience. In my work there is a focus on seemingly commonplace events, objects, and forms whose significance has been enhanced in an ambiguous statement. In a new context specific objects and materials function in relationships foreign to their identity. A certain credibility in this new identity makes them psychologically provocative. My use of objects reflects the influence of Jasper Johns, Robert Rauchenberg, and Rene Magrite. They used objects in an overtly confrontational manner. In my work there is a reserved atmosphere where the confrontation is denied. The impermanent, unprecious nature of the materials is a part of the fast changing, disposable attitude in my modem society. The imposing presence of the work contradicts impermanence, and this creates a paradox by presenting miscellaneous objects in a precious manner. Feelings of static confinement are tempered by unresolved spontaneity. These opposing qualities are subtle and achieve a form of coexistence. In content the use of human manipulation echos man's mimicry of natural order. Levels of order reflect my personal beliefs about their psychological functioning. I propose an ordered atmosphere of reserved human normalcy where tensions and contradictions arise, build, and expire.
Keywords: Collage; Mixed media (Art)